2020
DOI: 10.1186/s12960-020-00544-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of stress, anxiety and depression within front-line healthcare workers caring for COVID-19 patients: a systematic review and meta-regression

Abstract: Background Stress, anxiety, and depression are some of the most important research and practice challenges for psychologists, psychiatrists, and behavioral scientists. Due to the importance of issue and the lack of general statistics on these disorders among the Hospital staff treating the COVID-19 patients, this study aims to systematically review and determine the prevalence of stress, anxiety and depression within front-line healthcare workers caring for COVID-19 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
365
10
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(422 citation statements)
references
References 51 publications
26
365
10
21
Order By: Relevance
“…One review showed that 71.5% of healthcare providers reporting mild to severe symptoms of post-traumatic stress disorder (Carmassi et al, 2020 ). Another systematic review and meta-analysis showed that the prevalence of stress was 45%, depression 24.3%, and anxiety 25.8% in frontline healthcare workers caring for patients with COVID-19 (Salari et al, 2020 ). Resilience is the ability of an individual to withstand setbacks, adapt positively, and bounce back from adversity (Luthar and Cicchetti, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…One review showed that 71.5% of healthcare providers reporting mild to severe symptoms of post-traumatic stress disorder (Carmassi et al, 2020 ). Another systematic review and meta-analysis showed that the prevalence of stress was 45%, depression 24.3%, and anxiety 25.8% in frontline healthcare workers caring for patients with COVID-19 (Salari et al, 2020 ). Resilience is the ability of an individual to withstand setbacks, adapt positively, and bounce back from adversity (Luthar and Cicchetti, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses have highlighted that at least one-third of the populations worldwide have reported symptoms of depression, anxiety, stress, and insomnia during the early stage of the COVID-19 pandemic [ 1 , 2 ]. In contrast, these symptoms are more severe among people with pre-existing mental health problems [ 3 ], quarantined persons [ 2 ], COVID-19 patients [ 2 , 4 ], and health care professionals [ 5 , 6 , 7 ]. It is expected that the adverse mental health implications arising from the pandemic can be more prevalent and persistent than the infection itself, which deserves timely and joined global efforts for efficient and effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In dealing with COVID-19 frontline health workers, operating in complex and challenging work environments negatively influences their job satisfaction. 29,56 Physicians in Serbia who work with SARS-CoV-2-positive patients were less satisfied with their job and with professional preparedness for epidemics than their counterparts. The share of dissatisfied physicians in the study was higher than recent estimates, but dissatisfaction with the job in the public healthcare sector has a variable trend over the last 5 years.…”
Section: Discussionmentioning
confidence: 98%